تجلِّياتُ صورةِ الذَّاتِ في شعرِ الفرزدقِ (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
يحاولُ هذا البحثُ الوقوفَ عندَ تحليلِ المتنِ الشِّعريِّ، لشاعرٍ مخضرمٍ شهدَ فترةَ صدرِ الإسلامِ، وعاشَ العصرَ الأمويَّ، وفي تحديدِ الهدفِ؛ يحاولُ البحثُ تسليطَ الضّوءِ على أبرزِ ملامحِ الإبداعِ الأدبيِّ، وروائعه شعراً كان أو نثرا ً، وهو الذّاتُ الإنسانيّةُ المحرِّكُ والدَّافعُ لأيِّ إبداعٍ إنسانيٍّ . وهنا يعمدُ البحثُ، إلى فصلِ أبرزِ الملامحِ الذّاتيّةِ عندَ شاعرٍ مشهورٍ كالفرزدقِ، الّذي شكّلَ حالةً فريدةً في ساحةِ الإبداعِ الأدبيِّ الشّعريِّ، من خلالِ النّقائضِ التي دارت بينَه وبين شاعرِ البلاطِ الأمويِّ جرير . كلُّ ذلكَ يجري من خلالِ محاولةِ تلمّسِ أبرزِ جوانبِ هذه الذّاتِ والأثرِ الّذي تركتهُ في النّتاجِ الأدبيِّ العربيِّ . This paper attempts at focusing on analyzing the poetic structure of a pre-and-post-Islamic poet who witnessed and lived in the early Islamic and Umayyad Eras. With regard to the objective, the paper is intended to shed light on the major features and master pieces of literary output, be its prose or verse, which is the human ego, the driving force and dynamo behind any human creativity. In this regard, the paper attempts at categorizing the major subjective characteristics of a famous poet, such as Al-Farazdaq, who represented a unique phenomenon on the creative, literary, and poetic scene, through the poetic satirical exchanges with Jareer, the Umayyad poet laureate. All this is being dealt with through trying to trace the major characteristics of this ego and the impact it had left on the Arab poetic output.